Exploring Knowledge and Perspectives of Artificial Womb Technology in Canada and Australia: A Qualitative Multi-Methods Study - Hukku, Srishti (Université d'Ottawa / University of Ottawa, 2025)
A century ago, J.B.S. Haldane brought to life the concept of assisted reproduction by envisioning ectogenesis, that is gestation outside of the human body, as the future of science. Since then, the concept of artificial womb technology has featured in bioethical debates as well as in the public imagination through popular culture. Perhaps most importantly, the potential of artificial womb technology has influenced the development of related public policy all over the world. More specifically, in both Canada and Australia, the Assisted Human Reproduction Act and the Research Involving Human Embryos Act, respectively, criminalize ectogenesis. Recent advances in the development of precursors to artificial womb technology and related technologies have resulted in renewed interest in academic communities with respect to the potential implications of this technology. Nonetheless, much of the substantive debate and discussion on artificial womb technology over the last decade has happened beyond the reach of the general public. Decision-makers in Canada and Australia need to be equipped with data that shed light on views of the citizenry in the event that efforts to modernize legislative frameworks move forward to reflect current technological, health, legal, and socio-ethical realities. This thesis uses qualitative methods to explore the knowledge and perspectives of Canadian and Australian citizens with respect to artificial womb technology. In addition, this thesis examines the potential implications of artificial womb technology for the 14-day rule which prohibits embryo transfer, the impact on highly stigmatized health services, such as abortion, and already marginalized sexual and gender diverse populations.
Keywords: Artificial Womb Technology; Canada; Australia; Ectogenesis; Abortion; 14-day rule; 2SLGBTQIA+